Calibration of the rutting model in HDM 4 on the highway network in Macedonia - Slobodan Ognjenovic, Vladimir Okrepilov, Riste Ristov, Jovan Papic (E3S Web of Conferences, 2018)
Abstract The World Bank HDM 4 model is adopted in many countries worldwide. It is consisted of the developed models for almost all types of deformation on the pavement structures, but it can’t be used as it is developed everywhere in the world without proper adjustments to local conditions such as traffic load, climate, construction specificities, maintenance level etc. This paper presents the results of the researches carried out in Macedonia for determining calibration coefficient of the rutting model in HDM 4.